Transnational effectiveness of precautionary measures (Papeles, 2022)
International cooperation regarding provisional and protective measures is a matter of principle, though regulated in conventional and autonomous norms. Some aspects such as the control of the jurisdiction of the requesting court, the urgent competence of the judge in whose jurisdiction the person or thing to be protected is located, the non-review of the origin of the measure by the requested court, the guarantee, the private way of transmission of the rogatory letter and legalization have raised some problems, derived from the conventional or legal text, or the interpretation that the doctrine and jurisprudence make of them. Some ways of solution are suggested.
Keywords: Counterpreventive measure or guaranty; rogatory letter; preventive measures; judge or court of the State of destination; urgent competence of the judge